2018
DOI: 10.1080/14737167.2018.1512408
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and resource use among psoriasis patients treated with biologics

Abstract: The emergence of immune-modulating drugs such as biologics has altered the treatment landscape for psoriasis. However, their use presents high financial costs to patients and healthcare systems. Patient demographic and socioeconomic status may influence adherence to biologic medications and usage of healthcare resources. Areas covered: We performed a systematic literature review to summarize the available evidence pertaining to biologic medication adherence and resource use. PubMed was searched using the terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In total, nine treatment‐related factors were identified to have clear associations (change in or lack of efficacy, biologic type, concurrent therapies, rescheduling of appointments, affordability, side effects, and initial dosage, frequent follow‐up, history of adherence to any psoriasis medications). The presence of concurrent therapies and frequent follow‐up were positively correlated to higher adherence 4,12 . A change in or lack of efficacy, side effects, rescheduling of appointments, decreased affordability, and increased initial dosage were all associated with decreased adherence rates 4,8 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In total, nine treatment‐related factors were identified to have clear associations (change in or lack of efficacy, biologic type, concurrent therapies, rescheduling of appointments, affordability, side effects, and initial dosage, frequent follow‐up, history of adherence to any psoriasis medications). The presence of concurrent therapies and frequent follow‐up were positively correlated to higher adherence 4,12 . A change in or lack of efficacy, side effects, rescheduling of appointments, decreased affordability, and increased initial dosage were all associated with decreased adherence rates 4,8 .…”
Section: Resultsmentioning
confidence: 97%
“…Regarding biologic therapy specifically, three SRs were identified 4,8,12,13 . In total, nine treatment‐related factors were identified to have clear associations (change in or lack of efficacy, biologic type, concurrent therapies, rescheduling of appointments, affordability, side effects, and initial dosage, frequent follow‐up, history of adherence to any psoriasis medications).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous analysis of the current/ 18 preceding 26 study data demonstrated an absence of neutralizing anti‐brodalumab antibodies. Therefore, the lack of efficacy in non‐responders could be related to poor adherence, given that adherence to biologics is reported to be suboptimal 27 . Moreover, self‐administration of brodalumab was permitted from Day 1.…”
Section: Discussionmentioning
confidence: 99%
“…It may be influenced by different factors. Adherence can be higher when income increases, in richer geographic areas, or in psoriasis patients visiting rheumatologists (1,2) whereas it could decrease when additional comorbidities or stressful situations take place and when self-administered medication is prescribed (3,4). From March 2020 to date, we have faced the large-scale spread of SARS-CoV-2 virus, which has posed new challenges in the organization and operation of hospitals and pharmacy departments.…”
Section: Introductionmentioning
confidence: 99%